In vitro fermentation of selected xylo-oligosaccharides by piglet intestinal microbiota - Moura, Patrícia (2008)
The objective of this study was to compare the in vitro fermentability of xylo-oligosaccharides (XOS) with different degrees of polymerisation (DP) by the intestinal digesta collected in three distinct intestinal sections of the porcine intestinal tract: ileum, caecum, and distal colon. The studied oligosaccharides included commercial short-chain XOS (DP 2e5), and medium-chain (DP 2e14) and long-chain (DP 2e25) XOS obtained by autohydrolysis of brewery’s spent grain (BSG), corn cobs (CC) and Eucalyptus globulus wood (EUC). The oligosaccharide and monosaccharide consumption, lactate and short-chain fatty acids concentrations were correlated with shifts on PCR titres of Bacteroides/ Prevotella, Bifidobacterium and Lactobacillus/Pediococcus populations, by using group- and genus-specific primers. All tested XOS were extensively fermented by the piglet ileal, caecal and colonic microbiota. The rate of consumption of medium- and longchain XOS was notably reduced in the fermentations by the ileal inoculum as compared to commercial XOS. EUC XOS, CC XOS and commercial XOS supported an enhancement of bifidobacteria and lactobacilli replication in a first stage of the fermentations. Apparently this stimulation was not selective, because Bacteroides/Prevotella replication increased in a second stage of the fermentations, coincident in time with the highest consumption rates of some XOS mixtures tested. Mostly due to the slow fermentability by the ileal microbiota, medium-chain and long-chain XOS mixtures can be regarded as promising functional candidates suitable to act as distally fermentable substrates